PENGARUH KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI MIPA SMA NEGERI 5 PADANG - YEYEN FEBRINISA (Jurnal Edukasi dan Penelitian Matematika, 2021)
This study aims to determine the effect of emotional intelligence on student learning outcomes. The type of research used is a combination of Ex Post Facto and descriptive with a quantitative research approach. The population is students of class XI MIPA. The sample collection technique used purposive sampling, the sample of 71 respondents was taken. Data collection used emotional intelligence questionnaires and final exam scores in semester 1 of specialization in mathematics. The data analysis used descriptive statistical analysis and simple linear regression analysis with a significant level of 10%. The results of the calculation of descriptive statistical analysis for the emotional intelligence variable obtained an average of 81,37 categorized as moderate, and the mathematics learning outcomes variable obtained an average of 77,04 categorized as moderate. The results of the regression calculation obtained a P-value of 0.084 <α = 0,1, with a value of R2 = 4,27%, which means that emotional intelligence has an effect of 4.27% on mathematics learning outcomes. The conclusion in this study is that there is an effect of emotional intelligence on mathematics learning outcomes in class XI MIPA SMA Negeri 5 Padang. Keywords- emotional intelligence, learning outcomes, mathematics